1972
DOI: 10.1002/ajpa.1330370111
|View full text |Cite
|
Sign up to set email alerts
|

Head form and climatic stress

Abstract: Empiric evidence indicates that the general distribution of the cephalic index is explicable in terms of climatic adaptation. Based on a sample of 339 populations, the magnitude of the index is statistically different between zones of predominantly dry heat, wet heat, wet cold and dry cold. There is an inverse relationship between the mean cephalic index and temperature. It is argued that the occupation of cold climates is one of the circumstances increasing the frequency of brachycephaly through time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
10

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 3 publications
4
43
0
10
Order By: Relevance
“…Etler (1994: p. 112a) suggests the possibility that H. erectus from Zhoukoudian represents a "cold-adapted racial variation within the population structure of middle Pleistocene east Asia." Beals (1972) and Beals et al (1983) have suggested that climate can influence the shape of the skull, and contend that data shows a trend toward brachycephaly in colder areas. Data collected from H. erectus crania are consistent with this conclusion (Beals et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Etler (1994: p. 112a) suggests the possibility that H. erectus from Zhoukoudian represents a "cold-adapted racial variation within the population structure of middle Pleistocene east Asia." Beals (1972) and Beals et al (1983) have suggested that climate can influence the shape of the skull, and contend that data shows a trend toward brachycephaly in colder areas. Data collected from H. erectus crania are consistent with this conclusion (Beals et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a neutral signal in craniodental traits may be seen as largely unexpected, since many studies had previously focused on the effects of selective pressures and developmental plasticity in creating cranial shape variation (e.g., Beals 1972;Beals et al 1983Beals et al , 1984Franciscus and Long 1991).…”
mentioning
confidence: 99%
“…inter-group correlations, between cranial measurements and environmental variables in modern human populations because contemporary geographic variations in cranial measurements may be the results of adaptation to some environmental factors. Beals (1972), Guglielmino-Matessi et al (1979), Beals et al (1983Beals et al ( , 1984, Mizoguchi (1985), Kouchi (1986), and others, have investigated ecological correlations between the head shape and climatic variables, and confirmed that brachycephalic people live in higher latitudes or colder regions.…”
Section: Introductionmentioning
confidence: 86%